2008
DOI: 10.1007/s11606-008-0680-3
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Care for Decompensated Heart Failure: Comparable Performance between Academic Hospitalists and Non-hospitalists

Abstract: BACKGROUND: Hospitalists improve efficiency, but little information exists regarding whether they impact quality of care. OBJECTIVE:To determine hospitalists' effect on the quality of acute congestive heart failure care. DESIGN AND PARTICIPANTS:Using data from the Multicenter Hospitalist Study, we retrospectively evaluated quality of care in patients admitted with congestive heart failure who were assigned to hospitalists (n=120) or non-hospitalists (n=252) among six academic hospitals. MEASUREMENTS:Quality me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 26 publications
(33 reference statements)
0
18
1
Order By: Relevance
“…Previous analyses of the costs associated with care by hospitalists, compared to care by other types of physicians, have not taken into account the decreased liability costs that are likely associated with care provided by hospitalists. 25,26 In conclusion, contrary to concerns that have been raised, we found that hospitalists face a lower rate of malpractice claims when compared to other internal medicine physicians and specialties. However, we did find that care discontinuities may be resulting in liability risk due to communication and handoff-related errors.…”
Section: Schaffer Et Al | Liability Of Hospitalist Model Of Carecontrasting
confidence: 90%
“…Previous analyses of the costs associated with care by hospitalists, compared to care by other types of physicians, have not taken into account the decreased liability costs that are likely associated with care provided by hospitalists. 25,26 In conclusion, contrary to concerns that have been raised, we found that hospitalists face a lower rate of malpractice claims when compared to other internal medicine physicians and specialties. However, we did find that care discontinuities may be resulting in liability risk due to communication and handoff-related errors.…”
Section: Schaffer Et Al | Liability Of Hospitalist Model Of Carecontrasting
confidence: 90%
“…Although the present study was not intended to identify the cause for the paradoxical finding that patients cared by cardiologists had generally more favorable event rates compared with hospitalists and nonhospitalists, these findings resemble similar outcomes that resulted from previous studies comparing cardiologists to family physicians. 5 There may be several reasons for these to the findings observed in our study. The observation that patients cared for by noncardiologists had less severe HF symptoms, were more likely to have preserved left ventricular systolic dysfunction, and more likely to be elderly may (in part) explain increased readmission rates in these provider types compared with cardiologists as previously described, 9,10 although these variables did not seem to be significant predictors of adverse outcomes in the presence of provider type in the model.…”
Section: Discussionmentioning
confidence: 51%
“…13,14 UCSF Moffitt-Long Hospital is a 400-bed urban academic medical center which provides services to the City and County of San Francisco, an ethnically and linguistically diverse area. UCSF employs staff language interpreters in Spanish, Chinese and Russian who travel to its many outpatient clinics, Comprehensive Cancer Center, Children's Hospital, as well as to Moffitt-Long Hospital upon request; phone interpretation is also available when in-person interpreters are not available, for off hours needs and for less common languages.…”
Section: Patients and Methods Patient Population And Settingmentioning
confidence: 99%
“…Patient mortality information was collected as part of the MHT using the National Death Index. 14 Language data were collected from a separate patientregistration database (STOR) at UCSF. Information on a patient's primary language is entered at the time each patient first registers at UCSF, whether for the index hospitalization or for prior clinic visits, and is based generally on patient self report.…”
Section: Data Sourcesmentioning
confidence: 99%